Never work harder than your students and other principles of great teaching - Jackson, Robyn Renee (ASCD, 2018)
Some great teachers are born, but most are self-made. And the way to make yourself a great teacher is to learn to think and act like one. In this updated second edition of the best-selling Never Work Harder Than Your Students, Robyn R. Jackson reaffirms that every teacher can become a master teacher. The secret is not a specific strategy or technique, nor it is endless hours of prep time. It's developing a master teacher mindset--rigorously applying seven principles to your teaching until they become your automatic response: Start where you students are. Know where your students are going. Expect to get your students there. Support your students along the way. Use feedback to help you and your students get better. Focus on quality rather than quantity. Never work harder than your students. In her conversational and candid style, Jackson explains the mastery principles and how to start using them to guide planning, instruction, assessment, and classroom management. She answers questions, shares stories from her own practice and work with other teachers, and provides all-new, empowering advice on navigating external evaluation. There's even a self-assessment to help you identify your current levels of mastery and take control of your own practice. Teaching is hard work, and great teaching means doing the right kind of hard work: the kind that pays off. Join tens of thousands of teachers around the world who have embarked on their journeys toward mastery. Discover for yourself the difference that Jackson's principles will make in your classroom and for your students